Art & ecology now - Brown, Andrew, 1954- (Thames & Hudson, 2014)
The first survey of its kind to explore contemporary art that focuses on ecology. From land art and earthworks in the 1960s to conceptual art of the new millennium, ecology-focused art has been a prominent genre in the art world for decades. This book offers a look into the recent explosion in contemporary art that deals directly with nature, the environment, climate change, and ecology...
Pod názvem: with 343 illustrations, 338 in colour
Keywords: moderní umění; umění -- ekologie; umění a krajina; náměty, témata a motivy; modern art; art -- ecology; art and landscape; themes and motives; monografie; fotografické publikace; monographs; photographical works